2014
DOI: 10.1007/s10096-014-2270-0
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine treatment and outcome in pregnant women with high hepatitis B viral loads

Abstract: Perinatal transmission is the most common mode of hepatitis B virus (HBV) transmission and is a leading cause of chronic infection worldwide. Maternal treatment with lamivudine (LAM) can result in a rapid and significant reduction in HBV viral load (VL) and, thus, mitigate the risk of mother-to-child transmission (MTCT). The aim of this study was to retrospectively evaluate the safety of LAM treatment administered in the third trimester of pregnancy and determine the influence, if any, on infant outcome. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…FDA considers it a pregnancy Category C medication with no evidence of teratogenecity in animals. In 2014, Jackson et al (28) published a study in which 45 women met criteria for LAM treatment, and no cases of perinatal transmission occurred in infants born to mothers who received treatment. The authors concluded that LAM therapy in highly viremic CHB-infected pregnant women could help reduce the rate of vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
“…FDA considers it a pregnancy Category C medication with no evidence of teratogenecity in animals. In 2014, Jackson et al (28) published a study in which 45 women met criteria for LAM treatment, and no cases of perinatal transmission occurred in infants born to mothers who received treatment. The authors concluded that LAM therapy in highly viremic CHB-infected pregnant women could help reduce the rate of vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis B virus MTCT is more likely to occur when the mother has high levels of detectable virus during pregnancy; antiviral therapy works by reducing the viral load in pregnant women, thus reducing the likelihood of transmission. Antiviral therapy has been highly effective at reducing human immunodeficiency virus transmission, and the drugs that could be used in HBV-infected pregnant women are both safe in pregnancy and affordable [ 5 , 7 ]. Furthermore, providing antiviral therapy to viremic women may be more feasible than the follow-up and administration of HBIG to newborns, especially in limited-resource environments.…”
mentioning
confidence: 99%
“…There are many reports about the rate of the transmission of the HBV infection during pregnancy and also understanding of the mechanisms of the transmission of the infection from mother to child. All these studies have sought to implement policies on maternal screening and infant follow-up as well as mechanisms to minimize the transmission rate (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Here, we aimed to review the ways for the prevention of this infection from mother to child and research the new guidelines.…”
Section: Contextmentioning
confidence: 99%
“…There is evidence that antiretroviral drugs such as Lamivudine, Tenofovir, and Telbivudine can prevent vertical transmission when administered to women with a high HBV viral load in the third trimester (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). It has been reported that mothers who have a viral load more than HBV DNA levels ≥ 10 6 copies/mL are at greatest risk for the transmission of the HBV to their infants.…”
Section: For a Pregnant Woman With A Positive Hbsag Test In Her Prenamentioning
confidence: 99%